2018
DOI: 10.1371/journal.pone.0197366
|View full text |Cite
|
Sign up to set email alerts
|

Application of individual behavioral models to predict willingness to use modern contraceptives among pastoralist women in Afar region, Northern Ethiopia

Abstract: BackgroundUse of modern contraceptive methods reduces the risk of unwanted pregnancy, and is influenced by individual-level factors. Willingness to use modern contraceptive methods maybe a useful metric when considering health outcomes as it could predict health behaviors. Therefore, the current study aimed to assess the willingness of women to use modern contraceptives in Afar pastoralist communities.MethodsA community-based cross-sectional study was conducted from May 1 to 30, 2016. Three hundred forty-five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
19
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 19 publications
9
19
2
2
Order By: Relevance
“…Referring to WHO recommendation a woman without complications should have at least four antenatal visits, the first of which should take place during the first trimester [3]. However, our findings on institutional delivery were similar to previous studies [22,23,27]. Easy access to most health facilities, highly educated creating better awareness, and improving the infrastructure of urban than rural residents, led to better utilization of maternal health services.…”
Section: Discussionsupporting
confidence: 85%
“…Referring to WHO recommendation a woman without complications should have at least four antenatal visits, the first of which should take place during the first trimester [3]. However, our findings on institutional delivery were similar to previous studies [22,23,27]. Easy access to most health facilities, highly educated creating better awareness, and improving the infrastructure of urban than rural residents, led to better utilization of maternal health services.…”
Section: Discussionsupporting
confidence: 85%
“…Similarly, a positive relationship between using the traditional contraceptive method and teenage pregnancy was observed in the Somali and Afar regions. This might be because of a fear of disapproval by community members due to cultural and religious norms to use contraceptives, which in turn lead to early pregnancy [ 41 , 42 ]. This is again supported by another literature where women in the eastern part of Ethiopia is either free of any contraceptive or use traditional contraceptive method [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The self-efficacy aspect of SCT was also included. Perceived self-efficacy of women have been shown to predict modern contraceptive use in the previous studies done in Kenya, Ethiopia and Nigeria [42, 43]. Finally, we incorporated perceived barriers to FP use from HBM into the decision aid.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we incorporated perceived barriers to FP use from HBM into the decision aid. Other FP intervention studies using this theory have shown greater FP use among women with greater perceived benefits and lower perceived barriers [30, 42].…”
Section: Discussionmentioning
confidence: 99%